Metastasis of in situ solid papillary carcinoma of the breast to the lungs:a rare case report - Zhou, Jing; Wu, Minmin; Huang, Xiaoli; Liu, Keyu; Xu, Jingjing (Frontiers in Oncology, 2025)
Solid papillary carcinoma (SPC) of the breast is considered a special subtype of ductal carcinoma in situ (DCIS), characterized by distinctive histological features and growth patterns. Although SPC itself is not very common, it is particularly noteworthy that distant metastasis from its non-invasive form is highly uncommon. This contrasts sharply with infiltrative solid papillary carcinoma (ISPC), which lacks the typical myoepithelial cell layer seen in SPC and displays a map-like infiltrative growth pattern, often involving adipose and fibrous stromal infiltration. This study reports a case of a patient who was diagnosed with in situ SPC following a total mastectomy, and subsequently developed pulmonary metastatic ISPC five years later. The case supports the concept of a morphological continuum from in situ SPC to invasive carcinoma and highlights that even non-invasive SPC may possess the distant metastasis, albeit rarely. These findings provide new insights into the biological behavior of this rare breast cancer subtype.